To Study Knowledge Regarding Healthy Lifestyle Modifications in Middle-Aged Diabetic Population - Patil, Ketaki; Yadav, Trupti (Journal of Ecophysiology and Occupational Health, 2024)
Background: Lifestyle plays a significant role in helping patients with diabetes control their blood sugar levels. Understanding early complications to prevent further adverse effects from uncontrolled sugar levels and a worsening healthy lifestyle is a prerequisite to knowledge regarding healthy lifestyle modifications. Exercise therapy has long been recommended for use in the management and prevention of type 2 diabetes. Dietary habits play an important role in the control of blood glucose levels in diabetic patients. An increase in calorie intake leads to poor glycemic control. Stress levels can affect the increased glucose levels. Middle-aged adults are at increased risk of developing diabetes, and this population may benefit from targeted interventions to promote healthy lifestyle modifications. Therefore, a study is needed to assess the level of knowledge and awareness of middle-aged diabetic populations regarding healthy lifestyle modifications. Materials and Methods: A validated questionnaire was prepared on Google Forms and distributed among the diabetic population. Data was calculated automatically on Google spreadsheet. Results: Patients with diabetes exhibit little awareness of recommended lifestyle changes. A poor understanding of diabetes and its complications is demonstrated by 83.87 % of the population. 77.41% of persons have a poor understanding of dietary adjustments for diabetes. 86.02% of respondents exhibit insufficient awareness of physical exercise therapies for diabetes. 52.68% of people are unaware of how stress affects insulin secretion. Conclusion: According to the study’s findings, Given the early onset of diabetes problems, middle-aged diabetics have an increasing need for knowledge regarding appropriate lifestyle adjustments due to their higher risk of diabetes.